REDEFINISI KOMUNIKASI ADMINISTRASI - Zakaria Lantang Sukirno; Setyowati Karyaningtyas; Alma Mandjusri; Des Hanafi (Program Studi Administrasi Publik, 2024)
Multidisciplinarity between communication science/studies and administrative science has not been explicitly claimed within various literature. Whereas in fact, the subject of administrative communication has been long a discourse since the 1960s. So, how is the state-of-the art of administrative communication? This article aims to explore the development of administrative communication subject and to reveal the multidisciplinarity of communication science/studies and administrative science. The method used in this research is non-systematic stand alone review with traditional-narrative review technique. The result of the study reveals the refinery and redefinition of administrative communication.